Relative Energy Deficiency in sport in male athletes: A commentary on its presentation among selected groups of male athletes - Burke, L. M.; Close, G. L.; Lundy, B.; Mooses, M.; Morton, J. P.; Tenforde, A. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Low energy availability (LEA) is a key element of the Female Athlete Triad. Causes of LEA include failure to match high exercise energy expenditure (unintentional) or pathological behaviors of disordered eating (compulsive) and overzealous weight control programs (misguided but intentional). Recognition of such scenarios in male athletes contributed to the pronouncement of the more inclusive Relative Energy Deficiency in Sport (RED-S) syndrome. This commentary describes the insights and experience of the current group of authors around the apparently heightened risk of LEA in some populations of male athletes: road cyclists, rowers (lightweight and open weight), athletes in combat sports, distance runners, and jockeys. The frequency, duration, and magnitude of the LEA state appear to vary between populations. Common risk factors include cyclical management of challenging body mass and composition targets (including "making weight") and the high energy cost of some training programs or events that is not easily matched by energy intake. However, additional factors such as food insecurity and lack of finances may also contribute to impaired nutrition in some populations. Collectively, these insights substantiate the concept of RED-S in male athletes and suggest that a specific understanding of a sport, subpopulation, or culture may identify a complex series of factors that can contribute to LEA and the type and severity of its outcomes. This commentary provides a perspective on the range of risk factors that should be addressed in future surveys of RED-S in athletic populations and targeted for specific investigation and modification.